Iodospirocyclization of Tryptamine‐Derived Isocyanides: Formal Total Synthesis of Aspidofractinine. (17th October 2018) - Saya, Jordy M.; Roose, Thomas R.; Peek, Jarryt J.; Weijers, Bram; de Waal, Thomas J. S.; Vande Velde, Christophe M. L.; Orru, Romano V. A.; Ruijter, Eelco
Abstract: The N ‐iodosuccinimide‐mediated spirocyclization of tryptamine‐derived isocyanides to generate spiroindolenines is reported. The products contain both an imine and an imidoyl iodide as flexible handles for follow‐up chemistry. Nucleophilic addition typically occurs chemoselectively on the imine moiety with complete diastereoselectivity, providing opportunities for the construction of complex molecular frameworks. The synthetic potential of the method was showcased in the formal total synthesis of (±)‐aspidofractinine.